Glucocorticoids Shape Macrophage Phenotype for Tissue Repair - Desgeorges, Thibaut; Caratti, Giorgio; Mounier, Rémi; Tuckermann, Jan; Chazaud, Bénédicte (Frontiers in Immunology, 2019)
Inflammation is a complex process which is highly conserved among species. Inflammation occurs in response to injury, infection and cancer, as an allostatic mechanism to return the tissue, ant to return the organism back to health and homeostasis. Excessive, or chronic inflammation is associated with numerous diseases, and thus strategies to combat run-away inflammation is required. Anti-inflammatory drugs were therefore developed to switch inflammation off. However, the inflammatory response may be beneficial for the organism, in particular in the case of sterile tissue injury. The inflammatory response can be divided into several parts. The first step is the mounting of the inflammatory reaction itself, characterized by the presence of pro-inflammatory cytokines and the infiltration of immune cells into the injured area. The second is the resolution phase, where immune cells move towards an anti-inflammatory phenotype and decrease the secretion of pro-inflammatory cytokines. The last stage of inflammation is the regeneration process, where the tissue is rebuilt. Innate immune cells are major actors in the inflammatory response, of which, macrophages play an important role. Macrophages are highly sensitive to a large number of environmental stimuli, and can adapt their phenotype and function on demand. This change in phenotype in response to the environment allow macrophages to be involved in all steps of inflammation, from the first mounting of the pro-inflammatory response to the post-damage tissue repair.